Performance analysis of video codec (H.263+, H.264) for videoconferencing over wireless local area network (WLAN) - Withy Nurul Jannah, Mohd Hussein (2013)
Videoconferencing is widely use all over the world, whether on business corporate, distance learning, or as in video call. Market high demand on good video quality helps corporation in reducing financial needs on travelling, but keep the budget-in for bandwidth usage. High bandwidth or good compression techniques. Both maintain a high video quality. Videoconferencing have high sampling rate, to convert audio and video analog to digital signals. Therefore, there is need of high bandwidth to support the sampling rate. Inadequate bandwidth may lead to pixilation, where, in congested network, a sample can be received in out of sequences. Thus, undesirable video-image quality. In this research, H.263+ and H.264 will be use as video engine. A real device simulation is used to demonstrate the selection of video codecs with good quality of video resolution. Testbed are measure based on video resolution (240p, 480p, and 720p). The test is carry out in predefine wireless network (WLAN) whereby, performances are measure on MO score, packet jitter and packet loss. Convergence of applications (file sharing, video steaming and etc.) in internet put fluctuation in the network. Therefore, simulations are tested in optimum network (utilizing the bandwidth without any disturbance) and in 'converge' network (network with other traffic) to observe the behavior of each codec in different resolutions. A codec with high quality of video resolution is expected to perform in the simulations.